Development of Kinemaster Diamond Application in Learning Islamic Religious Education at Ngadirejo 1 Elementary School in Blitar City - rohman, Miftakhul; Wahid, Achmad Nurdiansyah; Pangestu, Mukti (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
This research is a development of previous research entitled Kinemaster Pro V4 application development which is the same application with only a slight difference in appearance. This application is on an Android cellphone so it is easy to use. Islamic religious education as the material used in this study and fifth grade students of SDN Ngadirejo 1 Blitar City on PAI material. The development of learning videos was carried out as a solution to the difficulties of learning PAI and the lack of use of learning media to assist teachers in the PAI learning process. The type of research used is research and development (R&D) using the ADDIE model which consists of five stages, namely the analysis, design, development, implementation, and evaluation stages. The data collection instrument was a validation sheet given to three validators. The data analysis technique is by calculating the validation assessment score using the average score validity index (r). The results showed that the Kinemaster Diamond-based learning video on PAI material in class V SDN Ngadirejo 1 developed met the valid criteria from the validated aspects including video display aspects (graphics), program aspects, learning aspects, and curriculum aspects with a validity index of 3.80. Keywords: Kinemaster Diamond Application, Learning